Modelling the biogeographic boundary shift of Calanus finmarchicus reveals drivers of Arctic Atlantification by subarctic zooplankton - Freer, Jennifer; Daase, Malin; Tarling, Geraint A. (Global Change Biology, 2021)
Biological communities in the Arctic are changing through the climate-driven encroachment of subarctic species. This “Atlantification” extends to keystone Calanoid copepods, as the small-bodied Calanus finmarchicus increases in abundance in areas where it overlaps with larger Arctic congeners. The environmental factors that are facilitating this shift, whether related to optimal conditions in temperature or seasonality, remain unclear. Assessing these drivers at an Arctic-wide scale is necessary to predict future ecosystem change and impacts. Here we have compiled range-wide occurrences of C. finmarchicus and a suite of seasonal biophysical climatologies to build a boreo-Arctic ecological niche model. The data set was divided into two eras, 1955–1984 and 1985–2017, and an optimized MaxEnt model was used to predict the seasonal distribution of the abiotic niche of C. finmarchicus in both eras. Comparing outputs between eras reveals an increase in habitat suitability at the Arctic range edge. Large and significant increases in suitability are predicted in the regions of the Greenland, Labrador, and Southern Barents Seas that have experienced reduced seaice cover. With the exception of the Barents Sea, these areas also show a seasonal shift in the timing of peak habitat suitability toward an earlier season. Our findings suggest that the Atlantification of Arctic zooplankton communities is accompanied by climate-driven phenology changes. Although seasonality is a critical constraint to the establishment of C. finmarchicus at Arctic latitudes, earlier sea-ice retreat and associated productivity is making these environments increasingly favorable for this subarctic species.